Screening for anxiety in patients with cancer: Diagnostic accuracy of GAD-7 items considering lowered GAD-7 cut-offs - Miriam Grapp; Till J. Bugaj; Valentin Terhoeven; Hans-Christoph Friederich; Imad Maatouk (PLoS ONE, 2025)
Background A standard questionnaire for generalized anxiety disorders is the GAD-7. Attempts to improve its screening capacity in oncological settings resulted in a discussion about lowering its cut-off. This study examines the diagnostic accuracy of the GAD-7 items depending on applied cut-offs and whether, similar to depressive symptoms, a distinction between somatic-emotional and cognitive items might be relevant. Patients and methods Screening data from 4705 patients with cancer who were treated at the outpatient clinic of the National Centre for Tumour Diseases in Heidelberg were analysed. For the individual GAD-7 items sensitivity, specificity, positive and negative predictive values, and Clinical Utility Index were determined for cut-off ≥ 7, ≥ 8, ≥ 10 and ≥ 15 in the GAD-7 questionnaire. Results The best overall diagnostic accuracy was found for a cut-off ≥ 8. The cognitive items had the best diagnostic accuracy for identifying severe GAD (cut-off ≥ 15), and the somatic-emotional items had the best diagnostic accuracy for identifying mild to moderate GAD (cut-off ≥ 7, ≥ 8 and ≥ 10). Conclusions Our data support the recommendation of lowering the GAD-7 cut-off in oncology settings and suggest that in anxiety disorders, a symptom overlap between the physical illness and a possible mental disorder should be considered.